Farmers’ Perception of Causes and Consequences of their Indebtedness in Haryana, India - Jakhar Babloo; Kait Rohtas; Kumar Vijay (Studia Ekonomiczne i Regionalne, 2022)
Subject and purpose of work: The study aims to highlight the perception of farmers regarding the causes and consequences of their indebtedness.